2012
DOI: 10.1001/jama.2012.13872
|View full text |Cite|
|
Sign up to set email alerts
|

Daily Sedation Interruption in Mechanically Ventilated Critically Ill Patients Cared for With a Sedation Protocol

Abstract: clinicaltrials.gov Identifier: NCT00675363.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
305
2
22

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(337 citation statements)
references
References 24 publications
8
305
2
22
Order By: Relevance
“…They concluded that ''The effectiveness of any new intervention to minimize sedation likely depends on the local usual care.'' 12 Interestingly, in the current report 6 (as stated above), only 22% of all sedative and opioid infusions were stopped and resumed as part of a planned daily interruption strategy (most were stopped in preparation for extubation or neurological assessment). This occurred despite the fact that these data were collected after the publication of the earlier trials suggesting that daily interruption was beneficial 7,9 but prior to the publication of the SLEAP trial 12 which showed no benefit.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…They concluded that ''The effectiveness of any new intervention to minimize sedation likely depends on the local usual care.'' 12 Interestingly, in the current report 6 (as stated above), only 22% of all sedative and opioid infusions were stopped and resumed as part of a planned daily interruption strategy (most were stopped in preparation for extubation or neurological assessment). This occurred despite the fact that these data were collected after the publication of the earlier trials suggesting that daily interruption was beneficial 7,9 but prior to the publication of the SLEAP trial 12 which showed no benefit.…”
mentioning
confidence: 71%
“…10,11 The largest RCT to test daily interruption of sedation was the SLEAP study 12 that randomized 430 patients in 16 Canadian and United States centres using protocolized sedation in all patients. In this trial, patients randomized to daily sedation interruption required more daily boluses and higher mean doses of opiates and benzodiazepines, and they did not achieve a reduction in the duration of mechanical ventilation or ICU length of stay.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Evaluate clinician compliance with 'once daily' versus 'at least twice daily' screening assessments and the potential for contamination in the 'once daily' arm, [3] Assess current practices related to sedation, analgesia and delirium management, and mobilization before conducting 'once daily' or 'at least twice daily screening' assessments of weaning readiness to quantify potential factors that may lead to performance bias in the future, planned, large scale weaning trial [4] Identify barriers (clinician and institutional) to recruitment into this study. [5] Classify trial participants as requiring (i) simple, (ii) difficult or (iii) prolonged weaning using the 'Task Force on Weaning' definitions [34].…”
Section: Release Trialmentioning
confidence: 99%
“…The value of DSI [5][6][7] remains unclear. The results of this current study could simply reflect the strong history in the Netherlands of good sedation practice including a relative sparing use of sedatives.…”
mentioning
confidence: 99%